2019
DOI: 10.3892/ol.2019.10297
|View full text |Cite
|
Sign up to set email alerts
|

ERCC6L promotes cell growth and invasion in human colorectal cancer

Abstract: Excision repair cross-complementation group 6 like (ERCC6L), a recently discovered DNA helicase, has been demonstrated to be highly expressed in a variety of human cancer types. However, the precise role of ERCC6L in colorectal cancer (CRC) remains unclear. The current study aimed to investigate the potential role of ERCC6L in the development and progression of CRC. Reverse transcription-quantitative polymerase chain reaction, western blot analysis and immunohistochemistry were used to detect the expression le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…Interestingly, a newly published article using siRNA to reduce the expression of ERCC6L has a significant inhibitory effect on the proliferation and colony formation of CRC cells. 41 These results suggest that ERCC6L can promote the growth and invasion of CRC cell. It further validates our analysis and shows that the use of bioinformatics for cancer analysis is very fast and effective.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Interestingly, a newly published article using siRNA to reduce the expression of ERCC6L has a significant inhibitory effect on the proliferation and colony formation of CRC cells. 41 These results suggest that ERCC6L can promote the growth and invasion of CRC cell. It further validates our analysis and shows that the use of bioinformatics for cancer analysis is very fast and effective.…”
Section: Discussionmentioning
confidence: 77%
“…In this study, the bioinformatics analysis of ERCC6L may play an important role in the occurrence and development of CRC. Interestingly, a newly published article using siRNA to reduce the expression of ERCC6L has a significant inhibitory effect on the proliferation and colony formation of CRC cells 41 . These results suggest that ERCC6L can promote the growth and invasion of CRC cell.…”
Section: Discussionmentioning
confidence: 95%
“…It plays wide roles in regulating cell division, cell proliferation and other biological processes and is considered as a genetic marker in the development of tumours . It was reported that ERCC6L was relevant to disease progression and poor prognosis in many types of cancer, such as breast, renal and colorectal cancer . High expression of ERCC6L plus its role in embryonic development and the involvement of remodelling centromeric chromatin remind us to hypothesize that it may play a key role in tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they identified that some special genes such as MAD2L, CCNB1 and BIRC5, which had a close relationship with ERCC6L were involved in the cell cycle pathway, thus ERCC6L may play an important role in neuroblastoma. Recently, Xie et al [ 26 ] found that ERCC6L was abnormal overexpressed in colorectal cancer (CRC) tissues and cell lines, and reducing ERCC6L expression in CRC cells significantly inhibited the proliferation, cell cycle progression, and arrested cell cycle at G0/G1 phase. These findings demonstrated that ERCC6L may exert an essential role in tumor growth and may be an efficient target for tumor detection, diagnosis and therapy.…”
Section: Discussionmentioning
confidence: 99%